Women in a Time of Crisis: Inequality of Roles in the Family During the Pandemic In Indonesia - Hasanah, Umdatul; Muassomah, Muassomah; Wijayati, Mufliha; Abdullah, Irwan (UIN Sunan Kudus, 2023)
The introduction of work from home policies, intended to reduce the spread of COVID-19, has added to women's burden and reinforced their domestic roles. This article seeks to show that the ongoing pandemic, which has resulted in families being confined to home, has been used to justify the creation of new burdens for women. To support this argument, this article relies on data collected through two methods: mapping online resources and interviews. Trends identified in online sources were confirmed through interviews with 22 women, as well as a focus group discussion with women leaders. This article shows that women have become responsible for more domestic duties during the pandemic, and their burdens have increased as a result. They are expected not only to handle domestic labor and childcare, but also to act as teachers. To achieve a deeper understanding, this article recommends using participant observation and in-depth interviews to obtain a broader understanding of women's experiences during the COVID-19 pandemic.